A Specific Dot-Blot Immunoassay for Newcastle Disease Serodiagnosis - Hemmatzadeh, Farhid; Sharifzadeh, Ali (International Journal of Poultry Science, 2006)
Dot-blot enzyme immunoassay (DB-EIA) was utilized for detection of Newcastle disease virus (NDV) specific antibodies in infected poultries. Velogenic strain of NDV virus was propagated in embryonated eggs and purified by using ultracentrifugation. Purified whole particle of virus was absorbed by rabbit anti B1 and La-Sota strains antibodies and tested by AGID method. A total number of 140 sera from experimentally infected and 850 sera from vaccinated, healthy and/or diseased chicks tested by HI and ELISA were used for investigating of specific NDV antibodies. HRPO-conjugated anti-chicken antibody was used to detect bound NDV antibodies using TMB as substrate. Statistical analyses were shown significant differences in results of DB-EIA, to HI and ELISA test to detection of specific anti-velogeni NDV antibodies. The assay proved to be a simple, inexpensive reliable and rapid tool for NDV serodiagnosis and differentiation between vaccination and disease.